The Effectiveness of Boron Preservatives to Prevent Dry-wood Termite Attack on Mahogany Sapwood - Aryati Larasati; Joko Sulistyo (Masyarakat Peneliti Kayu Indonesia, 2014)
Mahogany wood is utilized for many furniture products and construction purposes. The objective of this experiment was to prevent wood-destroying insects by using boron preservatives such as boric acid and borax. Materials used were mahogany sapwood planks (19 years) obtained from community forest in Kali Bawang District, Kulon Progo. Two preservation methods, i.e., hot-soaking (1, 2, and 3 hours) and the cold-soaking (12, 24, 36, and 48 hours) in 5% concentration, were used. The drywood termites (Cryptotermes cynocephalus Light) were used for observation. The result showed that the retention value ranges were 4.25 to 12.99 kg/m3 for cold-soaking method and 3.09 to 9.53 kg/m3 for heat- soaking method. Mortaliy rate and mass loss due to termite attacks ranged from 56.0 to 80.6 % (control values : 43.3%) and 850 to 1370 mg (control values : 1930 mg). Significant interaction between soaking time and the type of preservative was observed to discover its effect on the levels of retention (cold soaking) and mortality rate of termites (hot soaking). Boron preservatives tended to enhance the repellent properties than its toxicity.